Asymmetric Pulses in Cochlear Implants: Effects of Pulse Shape, Polarity, and Rate - Macherey, Olivier (Springer-Verlag, 2006)
Existing cochlear implants stimulate the auditory nerve with trains of symmetric biphasic (BP) pulses. Recent data have shown that modifying the pulse shape, while maintaining charge balance, may be beneficial in terms of reducing power consumption, increasing dynamic range, and limiting channel interactions. We measured thresholds and most comfortable levels (MCLs) for various 99-pulses-per-second (pps) stimuli. “Pseudomonophasic (PS)” pulses consist of a brief phase of one polarity followed immediately by a longer and lower-amplitude phase of the opposite polarity. We focused on a novel variant of PS pulses, termed the “delayed pseudomonophasic (DPS)” stimulus, in which the longer phase is presented midway between the short phases of two consecutive pulses. DPS pulse trains produced thresholds that were more than 10 dB lower than those obtained with BP pulses. This reduction was much greater than the 0- to 3-dB drop obtained with PS pulses and was still more than 6 dB when a pulse rate of 892 pps was used. A study of the relative contributions of the two phases of DPS suggested that the short, high-amplitude phase dominated the perceived loudness. This study showed major threshold and MCL reductions using a DPS stimulus compared to the widely used BP stimulus. These reductions, which were predicted by a simple linear filter model, might lead to considerable power savings if implemented in a cochlear implant speech processor.